MOS Short Form 36 and Oswestry Disability Index outcomes in lumbar fusion: a multicenter experience - Glassman, Steven; Gornet, Matthew F.; Branch, Charles; Polly, David; Peloza, John; Schwender, James D.; Carreon, Leah (The spine journal, 2006)
Patient-based quality of life scales have become a critical element of post-op assessment for lumbar fusion surgery. The most extensive outcomes data have been generated through FDA-regulated IDE trials for new technologies, which produce excellent data but are constrained by strict enrollment criteria and limited indications. This raises a question as to whether the excellent results seen in these IDE trials can be reproduced in standard clinical practice. The purpose of this study was to analyze surgical results based upon standardized outcome tools, across a spectrum of interventions, for one- and two-level lumbar spine fusion procedures. This study is a retrospective review of prospectively collected patient based outcomes data. Four hundred ninety-seven patients, who underwent 1- or 2-level lumbar spine fusion at five participating spine centers, utilizing a variety of surgical techniques. Enrollment criteria included available demographic, surgical and clinical outcome data. At a minimum, patients had pre-op and one year post-op SF-36 data. In many cases two-year post-op SF-36 data and concomitant Oswestry Disability Index (ODI) data was available. SF36 and ODI. The patient population included 270 females and 227 males, with a mean age of 47 years. Sixty-five percent (N=324) had one level fusions and 35% (N=173) had two level fusions. Demographic data collected included age, gender, BMI, surgical history, smoking history and work status. Data was analyzed with repeated measures analysis of variance (ANOVA). SF-36 Physical Composite Score (PCS) improved a mean 9.9 points at one year post-op and 9.5 points at two years post-op. ODI improved a mean 22.2 points at one year post-op and 22.1 points at two years post-op. SF-36 PCS data for surgical approach subgroups revealed greater improvement (p=.03) in the ALIF group as compared to the PSF, PLIF/TLIF, or 360° fusion groups (12.6 points vs. 8.8, 9.3, 8.4 points) at 1 year post-op. At 2 years post-op, there was greater improvement (p=.02) in the ALIF and PSF groups as compared to the PLIF/TLIF and 360° fusion groups (13.8 and 11.2 points vs. 7.7 and 6.3 points). SF-36 PCS data demonstrated similar baseline scores for patients with and without prior decompression, but a significantly greater rate of improvement (11.3 vs. 7.2 points, p=.002) for patients without prior lumbar decompression surgery. The ODI data indicated a significantly greater disability at baseline in the prior decompression group, with greater improvement (21.7 vs. 17.5 points) in patients without prior surgery. This study documents improved outcomes, based on SF-36 and ODI scores, in patients undergoing lumbar fusion for one and two level degenerative disc disease. The findings also demonstrate efficacy for all of the surgical techniques studied, suggesting that surgeons can appropriately select the surgical strategy with which they are most adept.